RTCi versus OSBC teaching method in eight-year medical program: a randomized, controlled educational research - Lu Wang; Ben Zhao; Xiaohui Wang; Minghao Guo; Lu Wang; Lei Dou; Yinan Sun (BMC Medical Education)
Abstract Background Under the standardized educational research model, a multicentre, randomized controlled educational research was conducted to compare the efficacy of the research, teaching and clinical integration (RTCi) and organ system-based curriculum (OSBC) teaching methods in the eight-year medical program. Methods A total of 230 eight-year medical program participants from two clinical colleges signed informed consent for educational research, were randomly divided into the RTCi teaching group (N = 115) and the OSBC teaching group (N = 115) and underwent a one-year study under different teaching methods. The two groups were compared in terms of on-schedule graduation, the number of papers published per student, grade-weighted scores and objective structured clinical examination (OSCE) scores. Results The 230 participants were randomly divided into two groups. After one year of RTCi or OSBC teaching, the on-schedule graduation rate of the RTCi group was significantly higher than that of the OSBC group (90% vs. 70%, P = 0.006). The average number of papers published per student in the RTCi group was significantly greater than that in the OSBC group (1.3 vs. 0.7, P = 0.017). The study score of the RTCi group was greater than that of the OSBC group (85.6 vs. 85.2, P = 0.183), although the difference was not statistically significant. The OSCE score of the RTCi group was significantly greater than that of the OSBC group (93 vs. 90, P = 0.029). Conclusions In the multicentre randomized controlled teaching study, compared with the OSBC teaching method, the RTCi teaching method significantly improved the on-schedule graduation rate, the number of published papers and the OSCE scores of participants. In terms of study scores, the RTCi teaching method outperformed the OSBC method, with no statistically significant difference. The RTCi teaching method is more conducive to the training and comprehensive development of eight-year medical program participants. In practice, medical education institutions could consider adopting the RTCi teaching method to enhance educational outcomes. Future research should further explore its long-term impact on the career development of medical graduates to strengthen its applicability and sustainability in eight-year medical program.